Degradation of tannic acid by cold-adapted klebsiella sp NACASA1 and phytotoxicity assessment of tannic acid and its degradation products - Jadhav, Umesh; Kadu, Sudhir; Thokal, Nilesh; Padul, Manohar; Dawkar, Vishal V.; Chougale, Ashok D.; Salve, Abhay; Patil, Manoj (Environmental Science and Pollution Research, 2011)
The focus of the present study is to know the potential of bacterial isolate for tannic acid degradation at low temperature. Also, we tried to evaluate the suitability of phytotoxicity testing protocol for the determination of tannic acid toxicity. Screening for tannic acid degrading bacterial strains was carried out by using microbial isolation techniques. The 16S rDNA amplicon of the isolate was used to identify the isolate. The effect of different concentrations of tannic acid and its degradation products on germination of Vigna unguiculata was evaluated. The study was carried out to determine total sugar and starch content of the used seeds and even to check the presence of alpha-amylase activity during seed germination. The isolated bacterium was identified as Klebsiella sp NACASA1 and it showed degradation of tannic acid in 40 (+/- 0.85***) h at 15A degrees C and pH 7.0. A gradual decrease in root/shoot length was observed with increasing concentration of tannic acid. There was 95.11 (+/- 0.24**)% inhibition in alpha-amylase activity at 20,000 ppm tannic acid, as compared to control. No such effects were observed on germination, root-shoot length, and alpha-amylase activity with tannic acid degradation products. The results obtained confirmed that tannic acid may act as a toxic agent in plant cells. The simple biodegradation process presented in this study was found to be effective in reducing toxicity of tannic acid. Also, it reveals the potential of soil bacterium to degrade tannic acid at low temperature.
Keywords: Cold-adapted bacterium; Phytotoxicity; Tannic acid degradation

Hybrids of thienopyrimidinones and thiouracils as anti-tubercular agents: SAR and docking studies - Pisal, Mahesh M.; Nawale, Laxman U.; Patil, Manoj; Bhansali, Sujit G.; Gajbhiye, Jayant M.; Sarkar, Dhiman; Chavan, Subhash P.; Borate, Hanumant B. (European Journal of Medicinal Chemistry, 2017)
A number of hybrid molecules containing thienopyrimidinones and thiouracil moieties were designed, synthesized and tested against Mycobacterium tuberculosis H37Ra wherein it was observed that the compounds 11-1514 exhibited antitubercular activity in vitro (MIC 7.6–19.1 μg/ml, 12–35 μM) against dormant stage while compound 15 exhibited antitubercular activity in vitro against dormant (MIC 23.4 μg/ml, 41 μM) as well as active (MIC 25.4 μg/ml, 45 μM) stage. Structural modifications of compound 15 were carried out to study the structure-activity relationship and it was observed that compound 18 exhibited antitubercular activity comparable to compound 15. Cytotoxicity studies revealed that these molecules were non-toxic. The docking study of compound 15 showed that there was binding with the active site of mycobacterial pantothenate synthetase. Further docking studies led to the synthesis of the compounds 16 and 17 and the antitubercular activity screening results showed that these compounds have significant antitubercular activity. The compounds 15-18 (MIC 11–29 μg/ml, 19–51 μM) can be used as starting points for further optimization. The synthetic strategies used in the present work have potential to prepare a large number of compounds for further refinement of structures and the present results will be very useful in the development of a new class of antimycobacterial agents.